Shelf-life assessment of bread containing Cyperus rotundus rhizome aqueous extract with antimicrobial compounds identified by 1H-NMR - Algboory, Hussein L.; Kadum, Hana; Muhialdin, Belal J. (Elsevier BV, 2021)
This study evaluated the effects of Cyperus rotundus rhizomes aqueous extract on the shelf life of wheat bread. The aqueous extract strongly inhibited the growth of Aspergillus niger (78%), Penicillium spp. (89%) Bacillus subtilis (95%) and Bacillus cereus (90%). The C. rotundus extract had no significant (p≥0.05) effect on the moisture content (44.2–45.7) and water activity (0.86–0.87) of the wheat bread, significantly (p<0.05) increasing the phenolic content from 7.22 to 37.95 mg g−1 and decreasing the pH from 6.12 to 5.11. Fungal growth was observed on the treated bread after 11 days at 30 °C compared to 4 days for the control bread. However, the addition of the aqueous extract of C. rotundus affected the sensory attributes of the wheat bread but the bread was still considered acceptable by the trained panellists. In conclusion, the aqueous extract of C. rotundus rhizomes is a potential natural alternative to synthetic preservatives to extend the shelf life of wheat bread with high consumer acceptability.